Sweetened beverage tax implementation and change in Body Mass Index among children in Seattle - Jones-Smith, Jessica C.; Knox, Melissa A.; Chakrabarti, Suman; Wallace, Jamie; Walkinshaw, Lina; Mooney, Stephen J.; Godwin, Jessica; Arterburn, David E.; Eavey, Joanna; Chan, Nadine; Saelens, Brian E. (JAMA, 2024)
Importance Sweetened beverage taxes have been associated with reduced purchasing of taxed beverages. However, few studies have assessed the association between sweetened beverage taxes and health outcomes.